Pengaruh Greedy, Opportunity, Need Dan Exposure Terhadap Perilaku Kecurangan Akademik Mahasiswa - Ayu Rosma; Ai Nur Solihat; Gugum Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of greed, opportunity, need and exposure on student academic cheating behavior. This research uses a quantitative survey research method with an explanatory research design. The population in this study were active students from the Faculty of Teacher Training and Education, Siliwangi University class of 2020, totaling 1289 students. The sample collection technique used Proportional Random Sampling, and the sample size was 305 respondents. Data collection methods use questionnaires and data analysis techniques use multiple linear regression analysis, partial and simultaneous hypothesis testing. Based on the results of data processing, it was found that greedy did not have a significant effect on students' academic cheating behavior. Opportunity has a significant effect on academic cheating behavior. Need has a significant effect on academic cheating behavior. Exposure has no effect on academic cheating behavior. Then greedy, opportunity, need and exposure have a significant effect on students' academic cheating behavior.